Carbon-titanium-aluminum metal composite heat exchange core plate and preparation method thereof
By adopting the preparation method of carbon-titanium-aluminum metal composite materials, including pretreatment, sintering, hot rolling, stamping and surface modification treatment, the shortcomings of existing heat exchange core plates in corrosion resistance, lightweight, high stiffness, high strength and high conductivity are solved, and a higher performance heat exchange core plate is achieved.
Patent Information
- Application Number
- CN202411899617.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-04
AI Technical Summary
The existing heat exchange core plates have shortcomings in corrosion resistance, lightweight, high stiffness, high strength and high electrical and thermal conductivity, and are difficult to meet the increasing market demand.
The heat exchange core board sheet is prepared by carbon-titanium-aluminum metal composite material. By pretreating powder I and powder II, sintering, hot rolling, stamping, and surface modification treatment is carried out to form a board with high bonding strength and excellent corrosion resistance.
It significantly improves the corrosion resistance, lightweight and high thermal conductivity of the heat exchange core plate, while enhancing the stiffness and strength of the plate, meeting higher performance requirements.
Smart Images

Figure CN119554907A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon-titanium-aluminum metal composite materials, and in particular to a carbon-titanium-aluminum metal composite heat exchange core plate material and a preparation method thereof. Background Art
[0002] As the core component of the plate heat exchanger, the heat exchange core plate plays a key role in the heat exchange process. The heat exchange core plate, also known as the plate heat exchanger plate, is composed of a series of metal plates with a specific corrugated shape. These plates are closely arranged to form multiple thin rectangular channels, so that the cold and hot fluids can exchange heat through the plates in these channels. Its working principle is mainly based on heat conduction and fluid flow, and efficient heat transfer is achieved through heat conduction between plates and convection of fluids.
[0003] The heat exchange core plate has the following advantages: 1) High heat transfer coefficient: Due to the corrugated shape of the plate, the fluid presents a turbulent state in the flow channel, which increases the disturbance of the fluid and the heat transfer area, thereby improving the heat transfer coefficient. 2) Compact structure: The structural design of the heat exchange core plate greatly increases the heat exchange area per unit volume. The structure is compact and the volume is small, which is conducive to saving space and reducing installation costs. 3) Strong adaptability: By increasing or reducing the number of plates, the heat transfer area can be flexibly adjusted to meet the heat exchange requirements under different working conditions. 4) Convenient disassembly and maintenance: The heat exchange core plate usually adopts a detachable design, which is easy to disassemble and clean, reducing maintenance costs. 5) Small fouling coefficient: Due to the large flow disturbance, dirt is not easy to deposit on the heat exchange core plate.
[0004] With the continuous advancement of technology and changes in market demand, people have higher requirements for the corrosion resistance, light weight, high stiffness, high strength and high electrical and thermal conductivity of heat exchange core plates. Therefore, it is necessary to develop a carbon-titanium-aluminum metal composite heat exchange core plate material and a preparation method thereof to further improve the corrosion resistance, light weight, stiffness, strength and high electrical and thermal conductivity of the heat exchange core plate material. Summary of the invention
[0005] The object of the present invention is to provide a carbon-titanium-aluminum metal composite heat exchange core plate material and a preparation method thereof. The specific technical scheme is as follows:
[0006] In a first aspect, the present invention provides a method for preparing a carbon-titanium-aluminum metal composite heat exchange core plate, comprising:
[0007] Step S1, evenly spreading the first pretreated powder I in a mold under an inert atmosphere and compacting it; evenly spreading the second pretreated powder II on the powder I under an inert atmosphere and compacting it to form a blank;
[0008] Wherein, the powder I comprises titanium aluminum powder; the titanium aluminum powder comprises the following raw material components by weight: 50-60 parts of titanium powder and 40-50 parts of aluminum powder; the powder II comprises aluminum alloy powder;
[0009] Step S2, sintering the embryo;
[0010] Step S3, subjecting the sintered blank to multiple hot rolling processes to obtain a plate;
[0011] Step S4, stamping the electrode plate to obtain a core plate;
[0012] Step S5, performing surface modification treatment on the powder I surface of the core plate to obtain a plate; wherein the surface modification treatment includes sequentially performing sandblasting treatment, corrosion treatment and coating liquid modification treatment on the surface of the powder I away from the powder II; the coating liquid adopts the following raw material components in parts by weight: 2-5 parts of nano conductive graphite, 1-5 parts of polytetrafluoroethylene, 30-40 parts of acrylic binder, 1-2 parts of carbon nanotubes, and the balance is water.
[0013] Optionally, the powder I also includes cobalt powder and vanadium powder; the mass of the cobalt powder is 1%-5% of the mass of the titanium aluminum powder; the mass of the vanadium powder is 1%-5% of the mass of the titanium aluminum powder.
[0014] Optionally, the powder II also includes copper powder; the mass of the copper powder is 1%-2% of the mass of the aluminum alloy powder; and the aluminum alloy powder includes 6061 aluminum alloy powder.
[0015] Optionally, the first pretreatment includes first subjecting the powder I to a ball milling mechanical alloying treatment, and then adding a composite additive to the powder I and mixing the mixture; the mass of the composite additive is 1%-5% of the mass of the powder I;
[0016] The second pretreatment includes first subjecting the powder II to the ball milling mechanical alloying treatment, and then adding the composite additive to the powder II and mixing them evenly; the mass of the composite additive is 1%-5% of the mass of the powder I;
[0017] The composite additive comprises the following raw material components in parts by weight: 2-5 parts of phenolic resin, 2-3 parts of polyacrylic acid and 1-2 parts of polyethylene glycol;
[0018] The ball mill speed used in the ball milling mechanical alloying treatment is 200-300 rpm / min, and the ball milling treatment time is 60-120 min.
[0019] Optionally, in the embryonic material, the mass ratio of the powder I to the powder II is 1:2-1:5.
[0020] Optionally, the sintering treatment adopts a sintering temperature of 500-650° C. and a sintering time of 60-120 min.
[0021] Optionally, the rolling temperature used in the multiple hot rolling treatment is 450-550° C., and the deformation amount of each pass is 20%-30%;
[0022] The thickness of the electrode plate is 1-2 mm.
[0023] Optionally, before performing the surface modification treatment, the surface of the powder II needs to be shielded;
[0024] The corrosion treatment adopts alkali solution immersion corrosion, and the immersion corrosion time is 60-120 minutes;
[0025] The coating liquid modification treatment includes immersing the corroded surface of the powder I in the coating liquid for 10-30 seconds, followed by drying; the drying temperature used in the drying treatment is 110-130° C. and the drying time is 30-60 minutes.
[0026] In a second aspect, the present invention provides a carbon-titanium-aluminum metal composite heat exchange core plate material, which is prepared by the preparation method of the carbon-titanium-aluminum metal composite heat exchange core plate material.
[0027] Optionally, the corrosion current density of the plate is less than 1 μA / cm 2 , elastic modulus stiffness not less than 90GPa and contact resistance less than 10mΩ / cm 2 .
[0028] The application of the technical solution of the present invention has at least the following beneficial effects:
[0029] (1) The present invention provides a method for preparing a carbon-titanium-aluminum metal composite heat exchange core plate material, which can further improve the corrosion resistance, light weight and high electrical and thermal conductivity of the heat exchange core plate material. Specifically, the powder I used in step S1 of the present invention includes titanium aluminum powder, which can improve the corrosion resistance of the plate, and the powder II used includes aluminum alloy powder, which can achieve lightweighting of the plate; the sintering treatment in step S2, the multi-pass hot rolling treatment in step S3 and the stamping treatment in step S4 can improve the bonding strength between the interface of powder I and powder II; in addition, the plate after the sintering treatment in step S2 and the multi-pass hot rolling treatment in step S3 has the advantages of fine and uniform microstructure and strong plastic deformation ability, and is easy to be stamped and deformed into a core plate in step S4, which significantly reduces the cost; the surface modification treatment in step S5 can obtain a coating with strong adhesion, strong corrosion resistance and high thermal and electrical conductivity, wherein the sandblasting treatment can form pits on the surface of powder I, the corrosion treatment can form micro-nano pores inside the pits, and the coating liquid modification treatment can form a high-strength interface bonding force between the coating liquid and the pits and the micro-nano pores inside the pits, thereby improving the adhesion of the coating; the coating is a carbon structure coating, which can further improve the thermal conductivity, electrical conductivity and corrosion resistance of the coating.
[0030] (2) The present invention provides a method for preparing a carbon-titanium-aluminum metal composite heat exchange core plate, which can further improve the stiffness and strength performance of the heat exchange core plate. Specifically, the 6061 aluminum alloy powder used in powder II can improve the stiffness of the plate after sintering; the copper powder added to powder II can further improve the stiffness and strength performance of the plate through solid solution strengthening after sintering.
[0031] (3) In the preparation method of the present invention, the mass ratio of powder I to powder II is controlled to be 1:2-1:5, so that a thinner powder I layer can be produced. After the surface of the powder I layer is modified, the corrosion current density can be reduced to less than 1 μA / cm 2 , achieving excellent corrosion resistance.
[0032] (4) The corrosion current density of the carbon-titanium-aluminum metal composite heat exchange core plate prepared by the present invention is less than 1 μA / cm 2 , elastic modulus stiffness not less than 90GPa and contact resistance less than 10mΩ / cm 2 .
[0033] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0035] Figure 1 This is a scanning electron microscope image of Example 1 after corrosion treatment. DETAILED DESCRIPTION
[0036] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0037] Embodiment 1:
[0038] See also Figure 1 , a method for preparing a carbon-titanium-aluminum metal composite heat exchange core plate, comprising:
[0039] Step S1, evenly spreading the first pretreated powder I in a mold under an inert atmosphere (specifically nitrogen) and compacting it; evenly spreading the second pretreated powder II on the powder I under an inert atmosphere (specifically nitrogen) and compacting it to form a blank;
[0040] Wherein, the powder I comprises titanium aluminum powder; the titanium aluminum powder is a raw material component of the following mass parts: 50-60 parts (specifically 52 parts) of titanium powder and 40-50 parts (specifically 48 parts) of aluminum powder; the powder II comprises aluminum alloy powder;
[0041] Step S2, sintering the embryo;
[0042] Step S3, subjecting the sintered blank to multiple hot rolling processes to obtain a plate;
[0043] Step S4, stamping the electrode plate to obtain a core plate;
[0044] Step S5, performing surface modification treatment on the powder I surface of the core plate to obtain a plate; wherein the surface modification treatment includes sequentially performing sandblasting treatment, corrosion treatment and coating liquid modification treatment on the surface of the powder I away from the powder II; the coating liquid adopts the following raw material components in parts by weight: 2-5 parts of nano-conductive graphite (specifically 5 parts), 1-5 parts of polytetrafluoroethylene (specifically 5 parts), 30-40 parts of acrylic adhesive (specifically 30 parts), 1-2 parts of carbon nanotubes (specifically 1 part), and the balance is water (specifically 59 parts).
[0045] The powder I also includes cobalt powder and vanadium powder; the mass of the cobalt powder is 1%-5% (specifically 2%) of the mass of the titanium aluminum powder; the mass of the vanadium powder is 1%-5% (specifically 3%) of the mass of the titanium aluminum powder.
[0046] The powder II also includes copper powder; the mass of the copper powder is 1%-2% (specifically 2%) of the mass of the aluminum alloy powder; and the aluminum alloy powder is 6061 aluminum alloy powder.
[0047] The first pretreatment includes first subjecting the powder I to a ball milling mechanical alloying treatment, and then adding a composite additive to the powder I and mixing the mixture; the mass of the composite additive is 1%-5% (specifically 1%) of the mass of the powder I;
[0048] The second pretreatment includes first subjecting the powder II to the ball milling mechanical alloying treatment, and then adding the composite additive to the powder II and mixing them evenly; the mass of the composite additive is 1%-5% (specifically 1%) of the mass of the powder I;
[0049] The composite additive comprises the following raw material components in parts by weight: 5 parts of phenolic resin, 3 parts of polyacrylic acid and 2 parts of polyethylene glycol;
[0050] The ball mill speed used in the ball milling mechanical alloying treatment is 200-300 rpm / min (specifically 250 rpm / min), and the ball milling treatment time is 60-120 min (specifically 90 min).
[0051] In the embryonic material, the mass ratio of the powder I to the powder II is 1:5.
[0052] The sintering process adopts a sintering temperature of 500-650° C. (specifically 600° C.) and a sintering time of 60-120 min (specifically 90 min).
[0053] The rolling temperature used in the multi-pass hot rolling treatment is 450-550° C. (specifically 500° C.), and the deformation amount of each pass is 20%-30% (specifically 25%, and the deformation amount of each pass is measured by measuring the thickness difference of the plate before and after the rolling deformation with a vernier caliper, and calculating the relative value of the deformation);
[0054] The thickness of the electrode plate is 1-2 mm (specifically 1.5 mm).
[0055] Before performing the surface modification treatment, the surface of the powder II needs to be shielded;
[0056] The corrosion treatment adopts alkali solution immersion corrosion, and the immersion corrosion time is 120min; specifically, the alkali solution is 8mol / L sodium hydroxide solution; the corrosion treatment can form micro-nano pores, see Figure 1 ;
[0057] The coating liquid modification treatment includes immersing the corroded surface of the powder I in the coating liquid for 10 seconds, followed by drying; the drying temperature used in the drying treatment is 120° C. and the drying time is 50 minutes.
[0058] Embodiment 2:
[0059] Different from Example 1, the titanium aluminum powder is the raw material components in the following parts by mass: 60 parts of titanium powder and 40 parts of aluminum powder.
[0060] Embodiment 3:
[0061] The difference from Example 1 is that the titanium aluminum powder is the raw material components in the following parts by mass: 50 parts of titanium powder and 50 parts of aluminum powder.
[0062] Embodiment 4:
[0063] Different from Example 1, the coating liquid uses the following raw material components in parts by weight: 2 parts of nano-conductive graphite, 1 part of polytetrafluoroethylene, 40 parts of acrylic binder, 2 parts of carbon nanotubes, and the balance is water (specifically 55 parts).
[0064] Comparative Example 1:
[0065] Different from Example 1, the amount of copper powder in the powder II is zero.
[0066] Comparative Example 2:
[0067] Different from Example 1, the sintering temperature used in the sintering process is 450° C. and the sintering time is 60 min.
[0068] Comparative Example 3:
[0069] The difference from Example 1 is that the surface modification treatment in step S5 is eliminated.
[0070] Comparative Example 4:
[0071] Different from the first embodiment, the sandblasting process is eliminated.
[0072] Comparative Example 5:
[0073] Different from Example 1, the etching process is eliminated.
[0074] The plates prepared in Examples 1-4 and Comparative Examples 1-5 were sampled for corrosion current density test, tensile strength test, elastic modulus test, scratch test adhesion test and contact resistance test, respectively. The test results are shown in Table 1.
[0075] Corrosion current density test method: Tafel straight line extrapolation method is used for determination; the test results are used to measure the corrosion rate of the plate.
[0076] Tensile strength test method: Determine in accordance with the provisions of GB / T228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method".
[0077] Elastic modulus test method: Determine in accordance with the provisions of GB / T22315-2008 Tensile elastic modulus of metal materials (static method).
[0078] Scratch test adhesion test method: Determine in accordance with the provisions of JB / T 12721-2016 "Technical Specifications for In-situ Nanoindentation / Scratch Tester for Solid Materials".
[0079] Table 1 Test results
[0080]
[0081]
[0082] From the data in Table 1, we know that:
[0083] Compared with comparative examples 1-5, the plates prepared by embodiments 1-4 of the present invention have higher tensile strength, elastic modulus and adhesion, and lower corrosion current density.
[0084] In Comparative Example 1, the amount of copper powder used was zero, which significantly reduced the tensile strength and elastic modulus of the plate. This shows that adding an appropriate amount of copper powder can improve the tensile strength and elastic modulus of the plate.
[0085] Compared with Comparative Example 1, the tensile strength and elastic modulus of the plate are further reduced due to the too low sintering temperature in Comparative Example 2. This is because the sintering temperature is too low, and the alloy components cannot be fully dissolved, which further reduces the tensile strength and elastic modulus of the plate.
[0086] In Comparative Example 3, no surface modification treatment was performed, which resulted in a significant increase in the corrosion current density, causing the corrosion resistance of the plate to deteriorate significantly.
[0087] In Comparative Example 4, no sandblasting was performed, which resulted in a relatively increased corrosion current density and a relatively decreased adhesion. This indicates that no pits could be formed on the surface of the powder I without sandblasting, resulting in the coating liquid being unable to be effectively bonded to the surface of the powder I.
[0088] Compared with Comparative Example 4, no corrosion treatment was performed in Comparative Example 5, which further increased the corrosion current density and further decreased the adhesion. This indicates that without corrosion treatment, micro-nano pores cannot be formed inside the pits, which greatly weakens the bonding between the coating liquid and the surface of the powder I.
[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon-titanium-aluminum metal composite heat exchange core plate, characterized in that: include: Step S1, spreading the first pretreated powder I evenly in a mold under an inert atmosphere and compacting it; The second pretreated powder II is evenly spread on the powder I under an inert atmosphere and compacted to form a blank; Wherein, the powder I comprises titanium aluminum powder; the titanium aluminum powder comprises the following raw material components by weight: 50-60 parts of titanium powder and 40-50 parts of aluminum powder; the powder II comprises aluminum alloy powder; Step S2, sintering the embryo; Step S3, subjecting the sintered blank to multiple hot rolling processes to obtain a plate; Step S4, stamping the electrode plate to obtain a core plate; Step S5, performing surface modification treatment on the powder I surface of the core plate to obtain a plate; wherein the surface modification treatment includes sequentially performing sandblasting treatment, corrosion treatment and coating liquid modification treatment on the surface of the powder I away from the powder II; the coating liquid adopts the following raw material components in parts by weight: 2-5 parts of nano conductive graphite, 1-5 parts of polytetrafluoroethylene, 30-40 parts of acrylic binder, 1-2 parts of carbon nanotubes, and the balance is water.
2. The method for preparing the carbon-titanium-aluminum metal composite heat exchange core plate according to claim 1, characterized in that: The powder I also includes cobalt powder and vanadium powder; the mass of the cobalt powder is 1%-5% of the mass of the titanium aluminum powder; the mass of the vanadium powder is 1%-5% of the mass of the titanium aluminum powder.
3. The method for preparing the carbon-titanium-aluminum metal composite heat exchange core plate according to claim 1, characterized in that: The powder II also includes copper powder; the mass of the copper powder is 1%-2% of the mass of the aluminum alloy powder; and the aluminum alloy powder includes 6061 aluminum alloy powder.
4. The method for preparing the carbon-titanium-aluminum metal composite heat exchange core plate according to claim 1, characterized in that: The first pretreatment includes first subjecting the powder I to a ball milling mechanical alloying treatment, and then adding a composite additive to the powder I and mixing the mixture; the mass of the composite additive is 1%-5% of the mass of the powder I; The second pretreatment includes first subjecting the powder II to the ball milling mechanical alloying treatment, and then adding the composite additive to the powder II and mixing them evenly; the mass of the composite additive is 1%-5% of the mass of the powder I; The composite additive comprises the following raw material components in parts by weight: 2-5 parts of phenolic resin, 2-3 parts of polyacrylic acid and 1-2 parts of polyethylene glycol; The ball mill speed used in the ball milling mechanical alloying treatment is 200-300 rpm / min, and the ball milling treatment time is 60-120 min.
5. The method for preparing the carbon-titanium-aluminum metal composite heat exchange core plate according to claim 1, characterized in that: In the embryonic material, the mass ratio of the powder I to the powder II is 1:2-1:
5.
6. The method for preparing the carbon-titanium-aluminum metal composite heat exchange core plate according to claim 1, characterized in that: The sintering process adopts a sintering temperature of 500-650° C. and a sintering time of 60-120 min.
7. The method for preparing the carbon-titanium-aluminum metal composite heat exchange core plate according to claim 1, characterized in that: The rolling temperature of the multi-pass hot rolling treatment is 450-550°C, and the deformation amount of each pass is 20%-30%; The thickness of the electrode plate is 1-2 mm.
8. The method for preparing the carbon-titanium-aluminum metal composite heat exchange core plate according to claim 1, characterized in that: Before performing the surface modification treatment, the surface of the powder II needs to be shielded; The corrosion treatment adopts alkali solution immersion corrosion, and the immersion corrosion time is 60-120 minutes; The coating liquid modification treatment includes immersing the corroded surface of the powder I in the coating liquid for 10-30 seconds, followed by drying; the drying temperature used in the drying treatment is 110-130° C. and the drying time is 30-60 minutes.
9. A carbon-titanium-aluminum metal composite heat exchange core plate, characterized in that: The heat exchange core plate is prepared by the method for preparing the carbon-titanium-aluminum metal composite heat exchange core plate as described in any one of claims 1 to 8.
10. The carbon-titanium-aluminum metal composite heat exchange core plate material according to claim 9, characterized in that: The corrosion current density of the plate is less than 1 μA / cm 2 , elastic modulus stiffness not less than 90GPa and contact resistance less than 10mΩ / cm 2 .